Level of work stress and level of performance of community organizers in selected rural-based non-government organizations in the Province of Iloilo - Engada, Ma. Connie
This correlational study aimed to determine the relationship between perception on work stress and level of performance of community organizers working in selected rural-based Non-Government Organizations., The respondents of this study were thirty (30) community organizers working for at least one year in selected rural-based NGOs. The researchers used simple random sampling in choosing the respondents. Perception on work stress was measured using Work stress test and for the level of work performance, the researchers utilized Employee Performance Review. The hypothesis of this study was: There is significant relationship between level of work stress and level of performance of community organizers. The result of the study revealed that: 1) There is no significant difference between male and female respondents' level of work stress (tcomp=0.73<tcrit=2.048,p<0.05). 2)There is no significant difference between male and female respondents' evaluation of their level of performance (tcomp=0.59<tcrit=2.048,p<0.05). 3)There is a postive relationship between level of work stress and level of performance (r=17).